Selective CO2 Electroreduction to Multi-Carbon Products on Organic-Functionalized CuO Nanoparticles by Local Micro-Environment Modulation - Ren, Shan; Cao, Xi; Fan, Qikui; Yang, Zhimao; Wang, Fei; Wang, Xin; Bai, Licheng; Yang, Jian (Nano-Micro Letters, 2024)
Surface functionalization of Cu-based catalysts has demonstrated promising potential for enhancing the electrochemical CO2 reduction reaction (CO2RR) toward multi-carbon (C2+) products, primarily by suppressing the parasitic hydrogen evolution reaction and facilitating a localized CO2/CO concentration at the electrode. Building upon this approach, we developed surface-functionalized catalysts with exceptional activity and selectivity for electrocatalytic CO2RR to C2+ in a neutral electrolyte. Employing CuO nanoparticles coated with hexaethynylbenzene organic molecules (HEB-CuO NPs), a remarkable C2+ Faradaic efficiency of nearly 90% was achieved at an unprecedented current density of 300 mA cm−2, and a high FE (> 80%) was maintained at a wide range of current densities (100–600 mA cm−2) in neutral environments using a flow cell. Furthermore, in a membrane electrode assembly (MEA) electrolyzer, 86.14% FEC2+ was achieved at a partial current density of 387.6 mA cm−2 while maintaining continuous operation for over 50 h at a current density of 200 mA cm−2. In-situ spectroscopy studies and molecular dynamics simulations reveal that reducing the coverage of coordinated K⋅H2O water increased the probability of intermediate reactants (CO) interacting with the surface, thereby promoting efficient C–C coupling and enhancing the yield of C2+ products. This advancement offers significant potential for optimizing local micro-environments for sustainable and highly efficient C2+ production. Highlights: 1 Developing surface-functionalized catalysts with exceptional activity and selectivity for the electrocatalytic CO2RR to C2+ products under neutral electrolyte. 2 A remarkable C2+ FE of nearly 90% at an unprecedented current density of 300 mA cm−2 and maintain high FE (> 80%) at the wide current density performance (100–600 mA cm−2) in neutral environments using a flow cell as well as MEA electrolyzer. 3 Mechanical study reveals that reducing the coverage of coordinated K·H2O water increased the probability of intermediate reactants (CO) interacting with the surface, thereby promoting efficient C–C coupling and enhancing the yield of C2+ products.